Immunity to herpes simplex virus type 2: cell-mediated immunity in latently infected guinea pigs. - Donnenberg, A D (1980)
Cell-mediated (CMI) and humoral immunity to herpes simplex virus type 2 (HSV-2) were evaluated in infected strain 13/N guinea pigs with (45%) and without a history of recurrent herpetic disease. Virus was isolated by cocultivation from active herpetic lesions (9 of 10) as well as from the footpads (17 of 38), sacral ganglia (7 of 21), and sciatic nerves (1 of 21) of asymptomatic animals. Viral isolates grew in cells of human origin and were neutralized by hyperimmune anti HSV-2 sera. Humoral immunity measured by the presence of virus-neutralizing antibody was similar in both experimental groups. The involvement of CMI in recurrent disease was assessed by comparing lymphocyte transformation (LT) and leukocyte migration inhibition factor (LIF) responses in animals with a history of recurrent disease studied while asymptomatic (quiescent) and in animals without clinical evidence of recurrent disease (seropositive controls). Spleen cells from quiescent animals evidenced significant impairment of both LIF and LT responses as reflected in the requirement of higher antigen concentrations (up to 58-fold) and longer in vitro culture periods (up to 2.5 days) to mount responses comparable in magnitude to those observed in the seropositive control groups. Peripheral blood lymphocyte cultures obtained from quiescent animals showed similar impairment of LIF responses but displayed intact LT response. The data suggest that recurrent disease is associated with an impairment in the generation of anamnestic effector functions as reflected by altered kinetics and dose response patterns in in vitro secondary responses.